Accreditation of pharmacy programs and its impact on SPLE success and pharmacist readiness in Saudi Arabia - Almaghaslah, Dalia (Frontiers in Medicine, 2024)
The impact of pharmacy program accreditation on the Saudi Pharmacists Licensure Examination (SPLE) pass rates and overall pharmacist readiness was investigated.A cross-sectional retrospective study was conducted. Data on SPLE pass rates were obtained from the Saudi Commission for Health Specialties (SCFHS) 2024 report. Pharmacy colleges were categorized into five groups based on their students' average SPLE scores. Information on the national i.e.the Evaluation and Training Evaluation Centre (ETEC) and international i.e. the American Council for Pharmacy Education (ACPE) and the Canadian Council for Accreditation of Pharmacy Programs (CCAPP) accreditation status of these colleges was also collected.Higher average SPLE scores (mean=563, SE=43.4) were observed in accredited colleges (either national or international) compared to non-accredited colleges (mean=533, SE=33.6), with a significant difference noted (t(22) = -2.149, p = 0.042). Higher average SPLE scores (mean=581.8, SE=18.9) were also found in colleges with multiple accreditations compared to those with fewer or no accreditations (mean=548.02, SE=18.9), though this difference was not statistically significant (t(25) = -1.8, p = 0.086).It was demonstrated that accreditation, whether national or international, is associated with higher SPLE pass rates, indicating a positive impact on exam performance. National accreditation by ETEC alone was found to be sufficient for improving SPLE scores and ensuring pharmacist readiness, whereas dual or international accreditations did not provide additional benefits in this context.